Effect of acid oxidation treatment on adsorption properties of arc-discharge synthesized multiwall carbon nanotubes - Vicente, José Luis (2011)
The effect of nitric/sulfuric acid oxidation treatment on commercial arc-discharge multiwall carbon nanotubes was studied. Purification and structure modifications were assessed via Transmission Electron Microscopy and Thermogravimetric Analysis; while changes in adsorption properties were monitored by nitrogen and methane adsorption isotherms. After treatment, nitrogen isotherms present hysteresis loop and an increased BET surface area; while adsorption energies obtained from isosteric heat profiles revealed a marked decrease. We propose an explanation for these findings and use macroscopic experimental data to gain insight on acid oxidation effect on the material.